2017
DOI: 10.1002/2016gb005561
|View full text |Cite
|
Sign up to set email alerts
|

Annual cyclicity in export efficiency in the inner Southern California Bight

Abstract: The balance of marine autotrophy and heterotrophy regulates the ocean's ability to serve as a CO2 sink, as organic material produced by autotrophs sinks into the ocean interior to drive the biological pump. Marine ecosystems over the continental margins, especially coastal upwelling regions, account for a disproportionate amount of carbon export; thus, even small fluctuations in export in these regions can have a large impact on the global carbon cycle. In this study, we estimated the rate of gross oxygen prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 98 publications
3
20
0
Order By: Relevance
“…Haskell et al [2016b] found mixed layer NCP to be 10(15) mmol C m 22 d 21 in inshore California waters near Los Angeles during October 2013, lower than NCP during our study. GPP was 230(37) mmol C m 22 d 21 during the same time period [Haskell et al, 2017], which is similar to GPP during our study. Johnson [2010].…”
Section: Synthesis and Comparison With Prior Worksupporting
confidence: 87%
“…Haskell et al [2016b] found mixed layer NCP to be 10(15) mmol C m 22 d 21 in inshore California waters near Los Angeles during October 2013, lower than NCP during our study. GPP was 230(37) mmol C m 22 d 21 during the same time period [Haskell et al, 2017], which is similar to GPP during our study. Johnson [2010].…”
Section: Synthesis and Comparison With Prior Worksupporting
confidence: 87%
“…However, upwelling of low oxygen water at the coast violates the assumption that only net biological production and air-sea gas exchange affect the surface layer O 2 /Ar mass balance. Strong upwelling in coastal and equatorial regions can create waters undersaturated in O 2 /Ar (Haskell et al, 2017;Ianson et al, 2009;Tortell, 2005;Tortell et al, 2012), leading past studies to discard O 2 /Ar data within upwelling zones (Hendricks et al, 2004;Kaiser et al, 2005;Stanley et al, 2010). Jonsson et al (2013) used biogeochemical ocean circulation models to assess the O 2 /Ar derived NCP bias due to vertical exchange of oxygen across the base of the Southern Ocean mixed layer.…”
Section: Introductionmentioning
confidence: 99%
“…Piston velocity at the sea surface and vertical diffusive mixing are estimated using a wind speed-based approach (Figure 9, middle row) that calculates these rates daily, using a weighting procedure of the wind speed over the previous 15 days. The top row in Figure 9 presents NOP calculated from our box model of glider-measured oxygen concentration through time and piston velocity with black lines for both velocities reported by Haskell, Prokopenko, Hammond, et al (2016) and Haskell et al (2017), whereas the orange line uses Bakun Upwelling Index-based velocities. The ticks on the x axis mark the first of each month.…”
Section: Nop Estimates From Glider Oxygen Concentrationmentioning
confidence: 99%
“…The ticks on the x axis mark the first of each month. Black square symbols (and gray lines) are NOP rates (and uncertainties) reported by Haskell, Prokopenko, Hammond, et al (2016) and Haskell et al (2017). The middle row shows piston velocity (PV; black) and eddy diffusivity (K z ) at the mixed layer depth (dashed green) and euphotic depth (solid green) used in the NOP estimates in the top row, all calculated daily using a 15-day weighting procedure (Reuer et al, 2007).…”
Section: Nop Estimates From Glider Oxygen Concentrationmentioning
confidence: 99%
See 1 more Smart Citation